Gamification In Islamic Education Based Onglobal Zakat Game: Bijak Zakat Version 1.0 (GZG) - Azman Ab. Rahman; Ibrahim Hussin Ibrahim; Tengku Mansur Tengku Zainal Abidin; Ahmad Anis Muhd Fauzi (Usuli Faqih Research Centre PLT, 2024)
Non-Indexed Publication